A DETERMINATION OF EMPLOYEE PERFORMANCE BASED ON LEADERSHIP STYLE, DISCIPLINE, AND WORK CULTURE ON MOTIVATION AS AN INTERVENING VARIABLE - eni rosita (IJEBD (International Journal of Entrepreneurship and Business Development))
Purpose:knowing and analyzing the influence of leadership style on motivation, the influence of work discipline on motivation, the influence of work culture on motivation, the influence of leadership style, discipline, and work culture on motivation, knowing the influence of leadership style on performance, knowing the influence of discipline on performance, knowing the influence of work culture on performance, knowing the influence of leadership style, work culture, and work discipline on performance, and knowing the influence of work motivation on performance.